Deposição e caracterização de filmes finos de ZrMoN por magnetron sputtering reativo - Fontes Junior, Alberto Silva (2017)
ZrMoN thin films were deposited using reactive magnetron sputtering, with the aim to study the influence of Mo content on structure, mechanical properties and oxidation resistance. Three ZrMoN coatings, having concentrations of 23, 31 and 37 at.% , were selected. Different Ar/N2 ratios were applied on the deposition of pure ZrN, in order to obtain an stoichiometric film and replicate that parameter to the other samples. GIXRD analysis identified an ZrMoN crystalline film with an cfc structure. ZrMoN characteristic peaks followed the pure ZrN pattern, with displacements to larger angles. That fact is attributed to Mo accommodation on ZrN crystalline lattice, forming an substitutional type crystalline solid solution. Nanohardness tests results presented values of 33GPa for the sample with 23 at% of Mo, with posterior reduction after oxidation tests. XPS analysis confirm the formation of a biphasic structure of ZrN and MoN and shows indication of a formed solid solution of Mo inside ZrN, though with no intermetallic bonding between Zr and Mo. Oxidation tests were carried out in 500°C, 600°C and 700°C. Pure ZrN exposed to 500°C maintains the presence of grains related to ZrN phase, though in low intensity. ZrMoN thin films were completely oxidized in 500°C, in any Mo content.